Multi-Drug Resistance against Second-Line Medication and MicroRNA Plasma Level in Metastatic Breast Cancer Patients - Mehdi Dehghani; Samira Mokhtari; Hassan Abidi; Behnam Alipoor; Mohammad Amin Nazer Mozaffari; Hossein Sadeghi; Reza Mahmoudi; Mohsen Nikseresht (Iranian Journal of Medical Sciences, 2023)
Background: Circulating microRNAs (miRNAs) can help to predict the chemotherapy response in breast cancer with promising results. The aim of the present study was to investigate the relationships between the miR-199a, miR-663a, and miR-663b expression and chemotherapy response in metastatic breast cancer patients.Methods: This study is a case-control study performed at Yasuj University of Medical Sciences (2018-2021). The expression levels of miR-663a, miR-663b, and miR-199a in the serum of 25 patients with metastatic breast cancer versus 15 healthy individuals were determined by the real-time polymerase chain reaction method. The response to treatment was followed up in a 24-month period. All patients were treated with second-line medications. Two or more combinations of these drugs were used: gemcitabine, Navelbine®, Diphereline®, Xeloda®, letrozole, Aromasin®, and Zolena®. Statistical analyses were performed in SPSS 21.0 and GraphPad Prism 6 software. The expression levels were presented as mean±SD and analyzed by Student’s t test.Results: The results and clinicopathological features of patients were analyzed by t test. The statistical analysis showed that miR-663a expression was related to human epidermal growth factor receptor 2 (HER2) status and was significantly lower in the HER2+ than HER2- group (P=0.027). Moreover, the expression of miR-199a and miR-663b was significantly correlated with the response to treatment, in which the expression of miR-199a was higher in the poor-response group (P=0.049), while the higher expression of miR-663b was seen in the good-response group (P=0.009).Conclusion: These findings state that the high plasma level of miR-199a and the low plasma level of miR-663b may be related to chemoresistance in patients with metastatic breast cancer.